1991
DOI: 10.2170/jjphysiol.41.369
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of H+ Extrusion via Na+-H+ Exchange in Guinea-Pig Ventricular Papillary Muscle under Intracellular Acidic Condition.

Abstract: We investigated mechanisms by which intracellular pH was regulated under intracellular acidic condition in resting guinea-pig ventricular papillary muscles in vitro. Intracellular sodium ion activity (aiNa), intracellular and surface pH (pHi and pHs) were measured with Na(+)- and H(+)-selective microelectrodes and resting tension was measured. By exposure to 0 mM K solution aiNa and resting tension increased progressively while pHi decreased but reached the steady level of pH 6.95. pHs which was lower than ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Measurements of intracellular cation contents revealed that amiloride could inhibit cellular Na accumulation in the early stage of reperfusion and cellular Ca 2 accumulation in the late stage. It has been proposed that intracellular H accumulation due to ischaemia facil-itates Na /H exchange during reperfusion (7,9,12,15) and causes subsequent Ca 2 influx through Na /Ca 2 exchange (19,20). Hence, it seems likely that amiloride inhibited cellular Na accumulation through its blocking action on Na /H exchange in the early stage of reperfusion, and prevented consequent Ca 2 overload via Na /Ca 2 exchange in the late stage.…”
Section: Effects Of Amiloride On Changes In Intracellular Cation Contmentioning
confidence: 99%
“…Measurements of intracellular cation contents revealed that amiloride could inhibit cellular Na accumulation in the early stage of reperfusion and cellular Ca 2 accumulation in the late stage. It has been proposed that intracellular H accumulation due to ischaemia facil-itates Na /H exchange during reperfusion (7,9,12,15) and causes subsequent Ca 2 influx through Na /Ca 2 exchange (19,20). Hence, it seems likely that amiloride inhibited cellular Na accumulation through its blocking action on Na /H exchange in the early stage of reperfusion, and prevented consequent Ca 2 overload via Na /Ca 2 exchange in the late stage.…”
Section: Effects Of Amiloride On Changes In Intracellular Cation Contmentioning
confidence: 99%
“…The double barreled ion-selective microelectrodes were constructed and calibrated as described previously (8,34,35), using liquid-sensor cocktails (hydrogen ionophore Icocktail B, model 95293; Fluka Chemika-Biochemika, Buchs, Switzerland) for H+. Two capillaries were designated as tube A for a reference electrode measuring transmembrane potential and tube B for the ionic sensor.…”
Section: Double Barreled Ion-selective Microelectrodesmentioning
confidence: 99%
“…The acidic intracellular environment would favor the exchange of extracellular Na+ for intracellular H+ via Na+-H+ exchange, resulting in an abnormal gain of intracellular Na+ (5)(6)(7)(8). An accumulation of Na+ inside the cell would lead to subsequent Ca2+ entry via Na+-Ca 2+ exchange.…”
mentioning
confidence: 99%